Perspectivas ribeirinha sobre os impactos da construção de usinas hidrelétricas no rio Madeira em Rondônia - Steven J. Rainey; Maura C. Araújo Rainey (Confins)
During the past forty years, Rondônia has seen significant changes, beginning with construction of, BR 364, and the rapid expansion of the agricultural frontier into the southern and central portions of the state during the 1970s and 1980s. During this same time period, the Madeira River has also undergone significant changes, with increased settlement and urbanization along its margins, hydraulic dredging for gold, and the development of the Madeira River Waterway. The construction of the Santo Antônio and Jirau dams on the Upper Madeira River upstream from the state's capital of Porto Velho represents the latest of these transformations, one which has the potential to cause significant impacts on river environments and ribeirinho communities. Although communities directly in the path of dam construction and reservoir infilling were resettled, communities downstream from the dam were not, having been told that they would not be affected by its implementation. However, residents of the ribeirinho community of Vila São Sebastião and adjacent areas began noticing changes in the river and varzea environments soon after dam construction commenced. These observed impacts were intensified by the historic flooding that occurred during the spring of 2014, as were residents' concerns concerning their futures and that of their community. This paper will examine observed dam and waterway impacts on river environments and ribeirinho communities, as seen through the eyes of Vila São Sebastião's residents, and will assess those claims through the use of photographic documentation, supported by a review of the scientific literature on potential dam impacts.